Periodic solution of a discrete commensal symbiosis model with Hassell-Varley type functional response - Chen Shangming; Chong Yanbo; Chen Fengde (Nonautonomous Dynamical Systems, 2022)
A non-autonomous discrete commensal symbiosis model with Hassell-Varley type functional response is proposed and studied in this paper. Sufficient conditions are obtained for the existence of positive periodic solution of the system.